Enhancing Regional Revenue Growth through Hotel Tax Potential and Contribution in Malang City Tourism Areas - Ringga Ananta Putra; Mayowan, Yuniadi (Badan Perencanaan Pembangunan Kota Malang, 2026)
This study analyzes the potential and contribution of hotel tax to Local Own-Source Revenue (Pendapatan Asli Daerah/PAD) of Malang City during the 2020–2024 period. The research employs a descriptive qualitative approach, utilizing primary data obtained through interviews and observations, as well as secondary data sourced from the Regional Revenue Agency (Bapenda) and the Central Statistics Agency (BPS). The results indicate that the hotel sector possesses substantial tax potential, supported by the growing number of hotels and diversified hotel services such as restaurants, spas, parking facilities, and advertising. However, the realization of hotel tax revenue has not yet been optimal. Although hotel tax revenue increased from IDR 25.42 billion in 2020 to IDR 61.08 billion in 2023, before slightly declining to IDR 60.19 billion in 2024, its contribution to total PAD remained low, ranging from 4.58% to 7.71%, and was classified as “very low.” This condition is influenced by fluctuations in room occupancy rates, changes in tourist spending patterns, inaccurate turnover reporting by taxpayers, and limitations in tax supervision and e-tax system implementation. The study recommends strengthening technology-based supervision, enhancing the capacity of tax authority personnel, integrating hotel transaction systems with tax collection mechanisms, and combining persuasive approaches with law enforcement to improve taxpayer compliance. These measures are expected to optimize hotel tax revenue and strengthen the regional fiscal capacity to support sustainable public services.